2021
DOI: 10.1093/hmg/ddab356
|View full text |Cite
|
Sign up to set email alerts
|

Fetal alleles predisposing to metabolically favorable adiposity are associated with higher birth weight

Abstract: Background Higher birthweight is associated with higher adult BMI. Alleles that predispose to greater adult adiposity might act in fetal life to increase fetal growth and birthweight. Whether there are fetal effects of recently identified adult metabolically favourable adiposity alleles on birthweight is unknown. Aim We aimed to test the effect on birthweight of fetal genetic predisposition to higher metabolically favourable adult adiposity and compare that with the effect of fetal genetic pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…A GWAS analysis concerning birthweight performed by Luo et al [ 23 ] identified a variety of loci in both maternal and fetal genomes potentially affecting this parameter in four populations (Afro-Caribbean, European, Hispanic and Thai). Extensive meta-analyses [ 24 , 25 ], identified a variety of loci where fetal genotype was associated with birthweight and found their associations with height, body-mass index and some metabolic diseases in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…A GWAS analysis concerning birthweight performed by Luo et al [ 23 ] identified a variety of loci in both maternal and fetal genomes potentially affecting this parameter in four populations (Afro-Caribbean, European, Hispanic and Thai). Extensive meta-analyses [ 24 , 25 ], identified a variety of loci where fetal genotype was associated with birthweight and found their associations with height, body-mass index and some metabolic diseases in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Our identification of rare LoF variants in two genes, ACVR1C and INHBE , that have fetal associations with higher birth weight and also a more metabolically favourable body fat distribution in adulthood is in line with recent findings that common genetic variants in the fetus, which predispose to higher metabolically favourable adiposity in adulthood, are also associated with higher birth weight. Variants with greater effects on adiposity have greater effects on birth weight 55 and we therefore hypothesise that the birth weight effects of ACVR1C and INHBE are due primarily to fetal fat accretion rather than effects on lean mass. A fetal genetic predisposition to greater birth weight and later favourable body fat distribution may underlie epidemiological associations between greater skinfold thickness at birth and favourable metabolic outcomes in early childhood, especially when controlling for exposure to maternal glucose levels in utero 56 .…”
Section: Discussionmentioning
confidence: 91%
“…Conversely, the PGS for birth weight was positively associated with BMI SDS and waist SDS, which is in line with previous findings of shared genetic loci between birth weight and childhood obesity. 39 A study in adults found that birth weight increasing variants were associated with increased adiposity in adulthood, but favourable metabolic outcomes. 39 The PGS for birth weight was not associated with lipid related traits in the present study, in line with previous studies, 10 suggesting that the association between lower birth weight and an unfavourable lipid metabolism later in life may mainly be due to fetal programming effects, as opposed to genetic effects.…”
Section: Discussionmentioning
confidence: 99%